Sketchbook Pro digital painting essentials : create stunning professional grade artwork using Sketchbook Pro - Robles, Gil (Community experience distilled., 2013)
This book is an example-based guide that will help you create professional grade paintings using Sketchbook Pro. As you progress from one chapter to another, you will learn how to virtually draw visually stunning paintings that are digitally drawn but look exactly like orthodox artwork. If you have had prior experience in developing digital artwork and are looking to add to your knowledge, Sketchbook Pro Digital Painting Essentials is a guide that will help you seamlessly translate what you do with traditional media to digital media.